The gigA/gigB Genes Regulate the Growth, Stress Response, and Virulence of Acinetobacter baumannii ATCC 17978 Strain - Zhou, Hua; Gebhardt, Michael J.; Czyz, Daniel M.; Yao, Yake; Shuman, Howard A. (Frontiers in Microbiology, 2021)
Objective: This study aimed to investigate the roles of gigA/gigB and the involvement of ptsP in the growth, stress resistance, and virulence of Acinetobacter baumannii strain ATCC 17978. Methods: Deletion and in situ complementation of gigA/gigB were performed to investigate the roles of gigA/gigB in bacterial growth, stress resistance, evading macrophage defense, and killing of Galleria mellonella larva. Deletion of ptsP was conducted in the ΔgigAB mutant to investigate its involvement in gigA/gigB signaling. Results: The gigA/gigB deletion efficiency in the wild-type A. baumannii 17978 background was only 4.2%. In strains harboring a deletion of the ptsP gene and/or gigA/gigB complementation, the deletion efficiency was dramatically enhanced to 42.9–68.8%; suggesting that the gigA/gigB gene products are critical for the growth of A. baumannii ATCC 17978 under the conditions tested herein. Loss of gigA/gigB did not readily lead to the isolation of compensatory mutations in the genome of the mutant. An arabinose-inducible plasmid-based gigA/gigB complementation restored the growth of ΔgigAB mutant on media supplemented with 1% arabinose. Stress resistance experiments showed that loss of gigA/gigB did not affect antibiotic resistance, acid stress response, and zinc stress response of strain 17978. However, the ΔgigAB mutant exhibited a growth defect at high temperature. Importantly, plasmid-based gigA/gigB complementation or loss of ptsP restored the growth of the ΔgigAB mutant to wild-type levels. Furthermore, the ΔgigAB mutant exhibited growth and replication defects within murine macrophages and failed to kill G. mellonella. Conclusion: The gigA/gigB genes are important for the growth and virulence traits, but are dispensable for several stress-resistance survival phenotypes, of A. baumannii strain 17978. Complementation of the gigA/gigB deletion strains with an arabinose-inducible plasmid system or a strain harboring an additional deletion of the ptsP gene abrogrates the growth defects of ΔgigAB mutant. Additionally, the gigA/gigB genes contribute to macrophage killing evasion of 17978 and are required for killing G. mellonella.